Treating postpartum depression in a mother of a child with congenital heart disease: a multidisciplinary approach and its challenges - Zakaria, Rozanizam; Fadzil, Nor Asyikin; Idris, Siti Aisyah; Mohd Zain, Mohd Rizal; Kadir, Suhaida (Department of Community Health, Faculty of Medicine and Helath Sciences UPM, 2017)
Introduction: Post-partum depression is a common psychological morbidity among women following childbirth which associated with various consequences towards the mother, child, and family. The magnitude of the problem is more significant in cases where there are multiple psychosocial issues complicating the presentation. Case report: We report a case of a 24 years old Malay mother, with a poor socioeconomic background from a rural district of Kelantan, who presented with severe depression during pregnancy and postpartum period precipitated by multiple family conflicts and issues related to poor social support. The depression deteriorated further when her baby was later diagnosed to have ventricular septal defect requiring operative intervention at 3 months of age. She was admitted to the psychiatry ward with the involvement of multiple disciplinary teams including psychiatry, paediatrics, hospital social welfare unit, local government welfare agency and primary health care clinic in her local area. Conclusion: This case highlighted the importance of a multidisciplinary approach in managing postpartum depression especially in complex cases where multiple medical and psychosocial issues dominating the presentation. We also discussed various challenges that clinician should be aware of when managing such cases.